Vertebral Morphology in Partially Sympatric Dolphins: A 3D Approach - Marchesi, Maria C.; Mora, Matías S.; Dans, Silvana L.; Coscarella, Mariano A.; González-José, Rolando (Frontiers in Marine Science, 2020)
In cetaceans, increased body flexibility is associated with increased maneuverability, this affects the animal’s swimming speed and foraging behavior. A more stable body form is associated with fast swimming and wide turns. One factor that affects the flexibility of a cetacean’s body is the structure and interaction of its vertebrae. Differences in vertebral morphology confer different muscular insertion sites and affect mechanical properties of swimming muscles. We studied vertebral morphology in four closely related and partially sympatric dolphin species from the Southern Hemisphere: Commerson’s dolphin (Cephalorhynchus commersonii), Peale’s dolphin (Lagenorhynchus australis), the dusky dolphin (Lagenorhynchus obscurus) and the hourglass dolphin (Lagenorhynchus cruciger). The former two species are usually considered coastal, associated with complex habitats where foraging strategies require greater maneuverability; they also show plasticity in their prey preferences. The latter two species are considered fast-swimming cooperative feeders, with long distance movements reflecting prey availability in pelagic habitats. We employed three-dimensional (3D) geometric morphometric techniques and multivariate analyses to evaluate differences in vertebral morphology. Our analyses tested whether particular morphologies that limit or enhance flexibility were associated with preferred habitats and feeding strategies. We established links between morphology and behavioral patterns based on the biomechanical significance of specific vertebral morphological features. Principal component analyses (PCA) showed great differentiation between species in all the studied regions along the vertebral column. This was especially evident in the middle area, except in the case of dusky and hourglass dolphins which showed no discernible morphological difference in their mid-column vertebrae. PCA results were supported by statistically significant Mahalanobis distances (MD) between species. Species associated with complex habitats and behaviors possessed morphological features associated with greater flexibility of the column (i.e., spool-shaped vertebrae with short erect processes), whereas cooperative-feeder species possessed features associated with greater stability (i.e., disk-shaped vertebrae with long strongly bent processes). In these closely related and partially sympatric dolphins, vertebral morphology is distinctive and varies with the differential foraging strategies and habitat of each species. These findings reveal morphological plasticity among these dolphin species, highlighting the importance of behavioral complexity and of habitat use in the evolutionary development of morphological adaptations.